CEDERA OLAHRAGA PADA ATLET PROVINSI DKI JAKARTA (PENGARUH PEMAHAMAN PELATIH, SARANA – PRASARANA OLAHRAGA DAN METODE LATIHAN TERHADAP TERJADINYA CEDERA OLAHRAGA) - Junaidi Junaidi (Gladi : Jurnal Ilmu Keolahragaan, 2017)
Abstract The objectives of this research are to obtain information the effect of coach comprehension , sport facilities and training method on sport injuries at the Training Centres Athletes - National Sport Committee of DKI Jakarta Province periode 2009 – 2012. This study was conducted at DKI Jakarta Province by using survey method with path analysis applied in testing hypothesis. The number of 55 subdivisions as a sample is selected random sampling. The research findings are: (1) There is a non-direct effect of coach comprehension on sport injuries; (2) There is a non-direct effect of sport facilities on sport injuries; (3) There is a direct effect of training method on sport injuries; (4) There is a direct effect of coach comprehension on training method; (5) There is a direct effect of sport facilities on training method; (6) There is an effect of coach comprehension on sport injuries through the training method; (7) There is an effect of sport facilities on sport injuries through the training method. Key words; Coach Comprehension , Sport Facilities, Training Method and Sport Injuries.